2017
DOI: 10.1002/ejic.201700874
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Luminescence Sensors Assembled with Lanthanide and a Cyclotriveratrylene‐Based Ligand

Abstract: By using a cyclotriveratrylene‐based ligand 5,12,19‐trimethoxy‐6,13,20‐tricarboxy‐methoxy‐cyclotriveratrylene (H3L), four lanthanide‐based compounds, Eu(L)(DMF)2 (1), Tb(L)(DMF)2 (2), Gd(L)(DMF)2 (3), and Yb(L)(DMF)(H2O) (4), have been constructed. Compounds 1–3 are isostructural and show charming two‐bowl interlocked chains linked by L3– anions and Ln3+ cations. The chains are further linked by C–H···π interactions to form two‐dimensional supramolecular layers, respectively. In 4, L3– anions bridge Yb3+ ions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…In addition, the LOD of 1 towards MnO 4 – is 1.43 μ m ( δ = 0.23 ppm). As compared with the known rare earth and/or transition metal ion‐based chemsensors, the of K sv value of 1 in water system is comparable with the complexes with different structures [ Ln (L 3 )(DMF) 2 ] ( Ln = Tb and Eu), [Pb 3 (BPDP) 1.5 (Hbdc) 3 ], and {[Ba 3 La 0.5 (μ 3 ‐L 4 ) 2.5 (H 2 O) 3 (DMF)] · (3DMF)} n , and is much smaller than those of the complexes [Tb(TBOT)(H 2 O)](H 2 O) 4 (DMF)(NMP) 0.5 , [Pb(BPDP)], and In(OH)(bpydc)‐Eu (Table ) . Since these known sensors with various structures are constructed from different metal ions and organic ligands, it can be concluded that the quench constant can be governed by various factors.…”
Section: Resultsmentioning
confidence: 73%
“…In addition, the LOD of 1 towards MnO 4 – is 1.43 μ m ( δ = 0.23 ppm). As compared with the known rare earth and/or transition metal ion‐based chemsensors, the of K sv value of 1 in water system is comparable with the complexes with different structures [ Ln (L 3 )(DMF) 2 ] ( Ln = Tb and Eu), [Pb 3 (BPDP) 1.5 (Hbdc) 3 ], and {[Ba 3 La 0.5 (μ 3 ‐L 4 ) 2.5 (H 2 O) 3 (DMF)] · (3DMF)} n , and is much smaller than those of the complexes [Tb(TBOT)(H 2 O)](H 2 O) 4 (DMF)(NMP) 0.5 , [Pb(BPDP)], and In(OH)(bpydc)‐Eu (Table ) . Since these known sensors with various structures are constructed from different metal ions and organic ligands, it can be concluded that the quench constant can be governed by various factors.…”
Section: Resultsmentioning
confidence: 73%
“…The luminescent lifetimes are τ 1 =1.7798 ns (49.01%), τ 2 =6.1431 ns (50.99%) (χ 2 =1.006) for 1 , and τ 1 =1.7206 ns (64.93%), τ 2 =5.2109 ns (35.07%) (χ 2 =1.006) for 3 (Figure S8). Their short lifetimes should come from singlet emissions …”
Section: Resultsmentioning
confidence: 99%
“…For example, the series of isostructural luminescent coordination polymers [M(L22)(DMF) 2 ], where M = Eu, Tb, Gd and L22 is a carboxylate-decorated CTV ligand, reported by Ma et al, exhibit an intra-cavity host-guest association between a lanthanidecoordinated DMF and L22 3− ligand. 25 That lanthanide also binds to the carboxylate groups of the same L22 3− ligand. which occurs without structural changes.…”
Section: Intra-and Inter-network Host-guest Associations With Coordinated Guestmentioning
confidence: 99%
“…which occurs without structural changes. 25 A further example of a material with an intra-chain coordinated host-guest motif is found in {[Eu(L23)(DMF)(H 2 O)]•1.5(DMF)(H 2 O)} 18 which utilises a distinct carboxylate-decorated CTV ligand. The structure features a carboxylate-bridged Eu-dimer with terminal DMF and aquo ligands.…”
Section: Intra-and Inter-network Host-guest Associations With Coordinated Guestmentioning
confidence: 99%
See 1 more Smart Citation